Metoda inwentaryzacji lasu oparta na losowaniu warstwowym wykorzystująca model wzrostu drzewostanu - Bruchwald, Arkadiusz; Dmyterko, Elżbieta; Mionskowski, Marcin (Leśne Prace Badawcze, 2024)
The paper presents a new variant of the method for determining the stand volume of age classes in a forest district or inspectorate (subdistrict). The methodological basis for this variant of the method is a branch of mathematical statistics called the „representative method”, which is based on stratified sampling, similar to the variant of forest inventory currently used in forestry. In the new variant of the method, strata are formed based on the age of the main tree species and the stand volume, which is determined by the stand growth model, while in the variant currently used, strata are formed based on the stand’s main tree species and its age. In the new variant of the stand volume determination method, 13 stages are distinguished, which can be divided into the initial and the main part. First, data from the State Forest Information System (SILP) database are processed: the age of the stand’s main tree species and characteristics that allow to determine the volume of each stand of the forest district or inspectorate using a stand growth model. Based on the age and stand volume, strata for the forest district or inspectorate can be formed and the number of samples for each of these strata can be determined. The main part of the new variant of the method starts with the measurement of DBH and tree height on the sample plots. The results of these measurements are then processed using, for example, a stand growth model. The volume of individual strata, age classes, and the entire forest district is determined. When using a growth model, many other stand characteristics are also determined, including volume increment, degree of windthrow hazard, rotation, and 10-year size of final and intermediate fellings. The evaluation of the accuracy of the method was based on data from 73 forest inspectorates in Poland. This was preceded by studies on the dispersion measures of the sum of tree volume on sample plots of different sizes. The new variant of the forest inventory method proved to be about 30% more accurate than the previously used variant.